Letramento funcional em saúde de usuários da atenção primária de Altamira - PA - LIMA, Rafael Ileus Monteiro (2022)
Functional Health Literacy (LFS) refers to the knowledge, motivation and competence of patients to access, understand, evaluate and apply health information, in order to make judgments and make everyday decisions. In view of this scenario, measuring this health literacy (LS) is necessary because it makes possible the possibility of constructing proposals for calls and the specific conditions of populations and improving health results. This project seeks to analyze the functional health literacy level (FHL) of primary care users in the urban area of Altamira-PA. Method: Cross-sectional study which the data collections occurred between August 2018 and December 2019 in 12 FHU of urban area. The participants were interviewed to collect sociodemographic data’s information, was later applied a questionnaire based on Brazilian version of Short Test of Functional Health Literacy (S-TOFHLA), which is used as an instrument to FHL measurement. The Pearson’s correlation coefficient, the Qui-Square test, the G test, and the odds ratio were used to verify the correlation between S-TOFHLA punctuation and the sociodemographic data. Furthermore, a multiple regression analysis was made to predict the factors which affect in FHL. Finally, the ANOVA test has sought differences between the FHL users’ level in the family healthcare units analyzed. Results: 400 participants were included in the study, 50% presented adequate FHL, 16.5% bordering and 24.5% inadequate. The variable level of schooling, age and income were associated to FHL in the population who was studied, they predict, respectively in 46%, 26% and 17% of the performance in the S-TOFHLA test. The individuals low schooling and low income increase the risk of having unsatisfactory FHL in 5 and 4 times, in this order. Finally, differences between the users’ FHL level of the FHU were found. Conclusion: The urban area population of Altamira presented high unsatisfactory FHL prevalence. Therefore, with the aim to increase the positive health results, the region healthcare professionals must adapt their ways of communication and language to the FHU users’ needs, observing that the group adequacy can bring improvements to understanding information and give best conditions of cure and self-care.